Exploring the relationship between schoolbag weight and back pain in primary school children - Sara Gamareldein Abdalla Khalafalla; Yousif Omer Elgaili Yousif; M. Elghazali Abuelgassim E. Mustafa; Widad Alsheikh Mostafa Alsheikh; Hiba Gamareldin A. Khalafallah; Mohammed Mubarak Mohammed Ahmed; Hozifa Mohammedd Ali Abd-Elmaged (Journal of Orthopaedic Surgery and Research)
Abstract Background Schoolbag weight in schoolchildren is a recurrent and contentious issue in education and health. Excessive schoolbag weight can lead to back pain in children, which increases the risk of chronic back pain in adulthood. This study aims to explore the pain experienced by primary school children and identify the risk factors for back pain among them. Materials and methods This observational, descriptive, cross-sectional study was conducted among Omdurman locality in Sudan primary school students from November 1, 2020, to May 31, 2021. A multistage random sampling technique was used to select the sample. Four schools were chosen. A total of 384 students were enrolled. The data were collected using a questionnaire administered by the researcher and analyzed by SPSS version 26. Results A total of 384 students were included in this study. A total of 192 (50%) were female, and 192 (50%) were male. The ages of the respondents ranged from 7 to 13 years, and the mean age was 11.5 ± 2. 09) SD. More than half of the studied students reported back pain 200 (52.1%); 40 (20%) were females, and 160 (80%) were males. Regarding the Visual Analogue Scale (VAS) score, 129 (64.5%) students rated their pain mild. Most 170 (85%) took medication without medical consultation. More than half of 200 (52.3%) students carried a weight greater than 15% of their body weight, and no one carried a bag with a weight less than 10%. Most students reach school by walking, which takes 10–20 min. There was a significant statistical association between the presence of back pain and older student age, male sex, carrying a bag more than 15% of one’s body weight, carrying a bag by one shoulder or side handbag, holding a bag through a morning venue and reaching school by walking for 10–20 min. P value (0.000). Conclusion More than half of our students reported back pain 200 (52.1%); 40 (20%) were females, and 160 (80%) were males. This study highlights a strong link between the prevalence of low back pain and the lifting of heavy school bags in primary school students in the Omdurman locality. The weights of the students’ schoolbags were higher than the internationally accepted standards. Through this study we are aiming to raise awareness about the negative effects and consequences of carrying heavy schoolbags, and recommending proper scheduling of classes and providing lockers as well as transportations to decrease this phenomenon.